El uso del software GeoGebra en el aprendizaje de la función cuadrática en los estudiantes de 5to grado de secundaria: una mirada desde la teoría de registros de representación semiótica - Morales Medrano, Lourdes Karin (2022)
This research is focused on the use of the GeoGebra tool for teaching and learning the quadratic function with fifth grade high school students. Researchers such as Bello (2014) and Limaymanta (2017) state that students in the 5th grade of secondary school and those in the first year of higher education have low performance in learning the quadratic function, because the graphical constructions are made using only pencil and paper. This does not induce in the learning of reasoning and communication skills. The present study aimed to know how the use of the GeoGebra tool contributes to the teaching and learning of the quadratic function in 5th grade secondary school students. The approach was qualitative and the sample consisted of eight students. For this research we chose as a theoretical reference the Theory of Records of Semiotic Representation of Duval (1995). Based on the results obtained, it can be pointed out that the use of the GeoGebra Software positively influences the learning of the quadratic function, since through this software the student can achieve the conversion of the algebraic expression to its graphic representation or vice versa.